Mediatization of celebrities’ cultural dynamics: the case of Rosalia on Instagram - Bravo-Araujo, Andrea (2021)
This article analyses the process of cultural mediatization of celebrities, taking as a case study the self-presentation of the singer Rosalía (@rosalia.vt) on the social network Instagram. For this purpose, a double quantitative and qualitative analysis has been carried out of the 449 publications made by the singer between 1-1-2018 and 31-7-2020, the period in which she achieved international fame with the release of the album El Mal Querer. The descriptive statistical analysis of this sample allows us to determine the singer's posting patterns, the categories to which she associates her image and the use she makes of the affordances of this social network. The iconological analysis of the sample allows us to determine the cultural references that Rosalía associates with her image within a globalized, urban and flamenco-inspired context. This study concludes that Rosalía appears as a typical case of celebritization, as she strategically uses the media logic of social networks as a way of consolidating her personal brand, diversifying it beyond the field of music.